Enterprise risk management best practices from assessment to ongoing compliance - Marchetti, Anne M., 1963- (Wiley corporate F & A., 2012)
"High-level guidance for implementing enterprise risk management in any organizationA Practical Guide to Risk Management shows organizations how to implement an effective ERM solution, starting with senior management and risk and compliance professionals working together to categorize and assess risks throughout the enterprise. Detailed guidance is provided on the key risk categories, including financial, operational, reputational, and strategic areas, along with practical tips on how to handle risks that overlap across categories. Provides high-level guidance on how to implement enterprise risk management across any organization Includes discussion of the latest trends and best practices Features the role of IT in ERM and the tools that are available in both assessment and on-going compliance Discusses the key challenges that need to be overcome for a successful ERM initiative Walking readers through the creation of ERM architecture and setting up on-going monitoring and assessement processes, this is an essential book for every CFO, controller and IT manager"--